THE EFFECT OF THE ECONOMIC GLOBALIZATION ON THE ECONOMIC GROWTH IN BULGARIA (Revista Inclusiones, 2021)
The paper examines the impact of the economic globalization on the economic growth in Bulgaria forthe period 2007-2018. The aim of the tudy is to reveal the impact of the economic globalization onthe economic growth. The research of the link economic globalization and its influence on theeconomic growth is performed via generalized method of moments (GMM), descriptive analysis anddeductive approach. The conclusion that has been reached is that economic globalization has apositive impact on the economic growth for the period 2007-2018. The main channel of influence isthe international trade.